Percent-free prostate specific antigen is elevated in men on haemodialysis or peritoneal dialysis treatment. - Bruun, L; Björk, T; Lilja, H; Becker, C; Gustafsson, O; Christensson, A (2003)
BACKGROUND: Men with chronic renal failure evaluated for transplantation are often tested for prostate specific antigen (PSA) to detect prostate cancer. PSA occurs in several different molecular forms in serum: free PSA (fPSA) and complexed PSA (cPSA), the sum of which corresponds to total PSA (tPSA). In addition to tPSA, percent fPSA to tPSA (%fPSA) is widely used to enhance discrimination of benign disorders from prostate cancer. The low molecular mass of fPSA suggests elimination by renal glomerular filtration and that renal failure may significantly influence %fPSA. We evaluated whether established reference levels for %fPSA are applicable also to patients treated with haemodialysis or continuous ambulatory peritoneal dialysis (CAPD). METHODS: The study included 20 men on intermittent haemodialysis with low-flux membranes and 25 men on CAPD, without known history of prostate cancer. The control group included 3129 men without known prostate cancer. We analysed fPSA and tPSA in serum by dual-label immunofluorometric assays, from which we calculated %fPSA and cPSA. Serum levels of different PSA forms were adjusted for age and presented as geometric means. RESULTS: Percent fPSA was significantly higher in patients on either haemodialysis (39.5%) or CAPD (39.6%) compared with controls (28.1%). Haemodialysis patients, but not CAPD patients, had significantly higher mean levels of fPSA. Levels of tPSA and cPSA for haemodialysis or CAPD patients did not differ significantly compared with controls. CONCLUSIONS: Recommended reference ranges for %fPSA, based on men with normal renal function, do not apply to uraemic men on dialysis. In these men, a high %fPSA should not be considered as a sign of benign disease. This is clinically important in the evaluation of dialysis patients for transplantation, as %fPSA is often used as a tool for detection of prostate cancer.